Examining safety knowledge and attitudinal factors related to unsafe conduct among lathe operators - Chairani, Alfiah; Hartono, Hartono; Siregar, Santy Deasy; Siregar, Fadhilaturrizqie; Mujahidin, Mujahidin; Sabri, Ihsan; William, Andy; Hutabarat, Bartimeus Nicomama (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Background: Unsafe actions are a primary contributor to occupational accidents in industrial environments, yet the influence of worker-specific factors like knowledge and attitude requires continuous investigation. This study aimed to determine the association between Occupational Safety and Health (OSH) knowledge, attitude, and the prevalence of unsafe actions among lathe machine operators. Methods: A cross-sectional study was conducted involving 33 lathe machine operators at CV. Melpura Jaya Teknik. Data on demographic characteristics, OSH knowledge, OSH attitude, and unsafe actions were collected using a structured questionnaire. The relationships between variables were analyzed using the Chi-Square test, with the significance level set at p < 0.05. Results: The analysis revealed a highly significant association between OSH knowledge and unsafe actions (p < .001), as well as a significant association between OSH attitude and unsafe actions (p = .031). Notably, all participants with poor knowledge (100%) or an unsupportive attitude (100%) were found to engage in high-risk unsafe actions. Conversely, all workers with good knowledge or a supportive attitude were classified in the low-risk category. Conclusion: OSH knowledge and attitude are critical determinants of safe behavior among lathe machine operators. Deficiencies in these areas are strongly correlated with high-risk actions. Therefore, workplace safety interventions should adopt a dual approach, focusing not only on comprehensive knowledge-based training but also on fostering a positive safety culture to shape supportive attitudes.